Maternal gut microbiota during pregnancy and the composition of immune cells in infancy - Gao, Yuan; O’Hely, Martin; Quinn, Thomas P.; Ponsonby, Anne-Louise; Harrison, Leonard C.; Frøkiær, Hanne; Tang, Mimi L. K.; Brix, Susanne; Kristiansen, Karsten; Burgner, Dave; Saffery, Richard; Ranganathan, Sarath; et al. (Frontiers in Immunology, 2022)
Background: Preclinical studies have shown that maternal gut microbiota during pregnancy play a key role in prenatal immune development but the relevance of these findings to humans is unknown. The aim of this prebirth cohort study was to investigate the association between the maternal gut microbiota in pregnancy and the composition of the infant’s cord and peripheral blood immune cells over the first year of life. Methods: The Barwon Infant Study cohort (n=1074 infants) was recruited using an unselected sampling frame. Maternal fecal samples were collected at 36 weeks of pregnancy and flow cytometry was conducted on cord/peripheral blood collected at birth, 6 and 12 months of age. Among a randomly selected sub-cohort with available samples (n=293), maternal gut microbiota was characterized by sequencing the 16S rRNA V4 region. Operational taxonomic units (OTUs) were clustered based on their abundance. Associations between maternal fecal microbiota clusters and infant granulocyte, monocyte and lymphocyte subsets were explored using compositional data analysis. Partial least squares (PLS) and regression models were used to investigate the relationships/associations between environmental, maternal and infant factors, and OTU clusters. Results: We identified six clusters of co-occurring OTUs. The first two components in the PLS regression explained 39% and 33% of the covariance between the maternal prenatal OTU clusters and immune cell populations in offspring at birth. A cluster in which Dialister, Escherichia, and Ruminococcus were predominant was associated with a lower proportion of granulocytes (p=0.002), and higher proportions of both central naïve CD4+ T cells (CD4+/CD45RA+/CD31−) (p<0.001) and naïve regulatory T cells (Treg) (CD4+/CD45RA+/FoxP3low) (p=0.02) in cord blood. The association with central naïve CD4+ T cells persisted to 12 months of age. Conclusion: This birth cohort study provides evidence consistent with past preclinical models that the maternal gut microbiota during pregnancy plays a role in shaping the composition of innate and adaptive elements of the infant’s immune system following birth.